2002
DOI: 10.1016/s0896-6273(02)00874-7
|View full text |Cite
|
Sign up to set email alerts
|

S Cone Contributions to the Magnocellular Visual Pathway in Macaque Monkey

Abstract: The magnocellular visual pathway is believed to receive input from long (L) and middle (M), but not short (S), wavelength-sensitive cones. Recording from neurons in magnocellular layers of lateral geniculate nucleus (LGN) in macaque monkeys, we found that magnocellular neurons were unequivocally responsive to S cone-isolating stimuli. A quantitative analysis suggests that S cones provided about 10% of the input to these cells, on average, while L:M ratios were far more variable. S cone signals influenced respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 67 publications
4
75
2
Order By: Relevance
“…Thus, the diffuse bipolar cells convey S-cone signals to at least three types of ganglion cell: parasol, garland, and the small, bistratified cell. Because the brisk-transient (parasol) pathway projects strongly to cortical area MT, it might be an important source for the strong S-cone signals in MT (Seidemann et al, 1999;Chatterjee and Callaway, 2002), although MT apparently gets some S-cone input via P cells (Nassi et al, 2006 Figure 4. B, Reconstructed dendritic trees (tangential view) from the cells in Figure 6 showing profiles of overlying cone terminals.…”
Section: Diffuse Bipolar Types Distribute S-cone Signals To Multiple mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the diffuse bipolar cells convey S-cone signals to at least three types of ganglion cell: parasol, garland, and the small, bistratified cell. Because the brisk-transient (parasol) pathway projects strongly to cortical area MT, it might be an important source for the strong S-cone signals in MT (Seidemann et al, 1999;Chatterjee and Callaway, 2002), although MT apparently gets some S-cone input via P cells (Nassi et al, 2006 Figure 4. B, Reconstructed dendritic trees (tangential view) from the cells in Figure 6 showing profiles of overlying cone terminals.…”
Section: Diffuse Bipolar Types Distribute S-cone Signals To Multiple mentioning
confidence: 99%
“…Third, are non-midget ganglion cells truly "achromatic," i.e., excited by all three cone types? Some studies report that parasol cells lack S-cone input (Dacey and Lee, 1994;Sun et al, 2006), whereas others find strong S-cone input to the M pathway and area MT (Seidemann et al, 1999;Chatterjee and Callaway, 2002). Finally, if the fovea contains different types of non-midget ganglion cell, as shown by Golgi staining (Polyak, 1941;Kolb et al, 1992) and retrograde labeling (Dacey et al, 2003), how does their circuitry differ?…”
Section: Introductionmentioning
confidence: 99%
“…We estimated M and S contrast weights from the data using a linear-nonlinear (LNL) model (Appendix C) (Fig. 5B) (Chichilnisky, 2001;Chatterjee and Callaway, 2002;Chichilnisky and Kalmar, 2002;Zaghloul et al, 2003).…”
Section: Measuring Horizontal Cell M S Weights: Flicker Experimentsmentioning
confidence: 99%
“…In our analysis, we followed previous authors (Chatterjee and Callaway, 2002;Diller et al, 2004;Johnson et al, 2004;Horwitz et al, 2005) and derived photoreceptor weights using a contrast measure. These weights describe the relationship between the contrast of the stimuli and the response of the postreceptoral cells.…”
Section: Contrast Versus Intensity Weightsmentioning
confidence: 99%
“…The commonest organization found in cortical neurons, Ϯ [(S ϩ M) Ϫ L], was instead that of blue-OFF cells in the LGN, which might be the major source of S-cone input to the cortex. Chatterjee and Callaway (2002) suggested that S cones also contribute, in proportion to their prevalence in the retina, to the receptive fields of M-cells. We found evidence for variable S-cone input to M-cells: S-cone inputs were negligible in seven but substantial in four.…”
Section: S-cone Contributions To Receptive Fields In the Lgn And Cortexmentioning
confidence: 99%